PERBEDAAN PENURUNAN SUHU TUBUH ANTARA PEMBERIAN KOMPRES AIR HANGAT DENGAN TEPID SPONGE BATH PADA ANAK DEMAM - Arie Kusumo Dewi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: to analyze the differences in the provision of warm compresses and tepid sponge bath in a decrease in body temperature in fever children in the room Hijr Ismail RSI A Yani Surabaya Methods: The design used in this study is quasy experiment with pre-test and post-test design. The population in this study is children aged 1-7 years who have increased body temperature ≥38oC treated in Hijr Ismail RSI A Yani Surabaya. The total sample is 90 respondents were divided into three groups: the provision of warm water compresses, group tepid sponge bath, and a control group. Sample was taken by simple random sampling technique according to inclusion criteria. The independent variable is the provision of warm compresses and giving tepid sponge bath and the dependent variable is the temperature of the body. Data were collected by using a digital thermometer and recorded in the observation sheet. Data were analyzed using one-way ANOVA to determine differences between administration decreased body temperature warm compresses and tepid sponge bath. Results: The results of this study showed a difference between providing a decrease in body temperature warm compresses and tepid sponge bath, with a significance value (p) of 0.000. Conclusion: It was concluded that the administration of tepid sponge bath with warm water greater decrease in body temperature (0C 0.57) than that of warm water compresses at 0,430C.